2014
DOI: 10.1097/qad.0000000000000381
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Toll-like receptor 2 is significantly elevated in HIV-1 infected breast milk and inhibits HIV-1 induced cellular activation, inflammation and infection

Abstract: These results indicate novel mechanisms by which sTLR2 plays a critical role in inhibiting mother-to-child HIV transmission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(42 citation statements)
references
References 39 publications
2
40
0
Order By: Relevance
“…Given that multiple viruses induce immune activation via TLR2 as a means to facilitate entry ( 36 , 38 , 39 ), as well as our recent paper which showed that soluble TLR2 (sTLR2) directly interacted with HIV-1 structural proteins ( 45 ), we explored whether cellular expression of TLR2 increased cell-free HIV-1 integration and viral-induced inflammation.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Given that multiple viruses induce immune activation via TLR2 as a means to facilitate entry ( 36 , 38 , 39 ), as well as our recent paper which showed that soluble TLR2 (sTLR2) directly interacted with HIV-1 structural proteins ( 45 ), we explored whether cellular expression of TLR2 increased cell-free HIV-1 integration and viral-induced inflammation.…”
Section: Resultsmentioning
confidence: 99%
“…However, we previously demonstrated that following cART and subsequent decrease in viral load, TLR expression in previously untreated HIV-infected individuals normalized, thus suggesting that HIV itself may be involved in increased activation ( 12 ). Additionally, we recently showed that soluble TLR2 (sTLR2), which is found in human milk, other mucosal fluids, and systemically, inhibited HIV infection in vitro ( 44 ), through a direct interaction with HIV-1 structural proteins, and inhibited virally induced NFκB activation and inflammation ( 45 ). These findings led us to ask a rather simple but important question, namely, do HIV-1 structural proteins act as PAMPs for TLR2 and its heterodimers?…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…49 The binding of sTLR2 to HIV-1 proteins in HIV-1 infected mother breast milk prevent a TLR2-dependent increase in chemokine receptor 5 expression, thus resulting in significant reduction of HIV-1 infection. 50 The concentration of erythropoietin, a factor with trophic effects on infant gut epithelia studied within a cohort of antiretroviralnaïve HIV infected Tanzanian women, suggest a protective effect against MTCT. 51 HIV gag -specific IFN-γ cellular immune responses from breastmilk of these Tanzanian were prevalent and may contribute to protection from early HIV transmission.…”
Section: Breast Milk Constituents May Provide Inside Of the Post-par-mentioning
confidence: 99%